Miss Representation - Newsom, Jennifer Siebel, 1974-; Scully, Regina Kulik; Winfrey, Oprah; O'Donnell, Rosie; Rice, Condoleezza, 1954-; Ling, Lisa.; Pelosi, Nancy, 1940-; Couric, Katie, 1957-; Maddow, Rachel; Dawson, Rosario; Katz, Jackson; Kilbourne, Jean.; et al. (New York : Virgil Films & Entertainment, Inc., 2012)
Explores how mainstream media contributes to the under-representation of women in influential positions in America and challenges the media's limiting and often disparaging portrayals of women. Features commentary from many influential women in media and politics.
DVD; NTSC, Region 1; widescreen presentation, 1.78:1 aspect ratio.
English, with optional English subtitles.
Closed captioned.
In the title frames, the word "Misrepresentation" changes to "Miss representation."
Introduction, Oprah Winfrey, Rosie O'Donnell ; participants, Condoleezza Rice, Lisa Ling, Nancy Pelosi, Katie Couric, Rachel Maddow, Rosario Dawson, Jackson Katz, Jean Kilbourne, Gloria Steinem, Geena Davis, Margaret Cho, Erika Falk, Pat Mitchell, Caroline Heldman, Marissa Mayer, Gavin Newsom, Cory Booker, Jane Fonda, Dianne Feinstein, Catherine Hardwicke, Dee Dee Myers, Paul Haggis.
Editor/co-writer, Jessica Congdon ; co-producers, Claire Dietrich, Julie Costanzo ; original music, Eric Holland ; director of photography, Svetlana Cvetko.
Keywords: Women in mass media; Gender identity in mass media; Mass media -- United States -- Influence; Identity (Psychology) and mass media; Mass media and teenage girls; Mass media and children; Sex role in mass media; Mass media -- Social aspects -- United States; Women in popular culture -- United States; Body image in women -- United States; Women -- United States -- Attitudes; Women -- United States -- Social conditions -- 21st century; Leadership in women; Women in mass media; Gender identity in mass media; Leadership in women; Mass media -- Social aspects; Nonfiction films; Documentary films; Feature films